Pengertian Utang Sebagai Dasar Permohonan Pailit Dalam Yurisprudensi - Ginting, Jamin (LAW REVIEW, 2002)
The definition of debt is definitely important in avoiding bias interpretation. Without a Â debt definition in the Bankruptcy Act No. 4 Year 1998, it has created crosswise-opinions Â that cause no assurance of law in the view of creditor, debtor, judge and advocate involved in case of bankruptcy. In some decision of bankruptcy sentenced by Commercial Court and Supreme Court made definition of debt as the simple meaning but the other hand definition of debt as wide meaning.Â